Pengaruh Kinerja Keuangan terhadap Return Saham dengan Nilai Tukar (Kurs) sebagai Variabel Moderasi - Istiqomah Istiqomah; Mardiana Mardiana (Universitas Muria Kudus, 2020)
The purpose of this study was to determine the effect of liquidity ratios (CR), leverage ratios (DER) and profitability ratios (ROA) on stock returns with exchange rates (exchange rates) as a moderating variable on pharmaceutical subsector companies listed on the Indonesia Stock Exchange for the period 2013-2017. This type of research is quantitative research using secondary data. The method of collecting data from this research is documentation. The sample in this study were 7 companies listed on the Indonesia Stock Exchange in the period 2013-2017 using purposive sampling. This study uses the classical assumption test analysis method, F test, T test and the Moderated Regression Analysis (MRA) Test to test the data examined. The results of this test indicate that liquidity, leverage and profitability have an influence on stock returns simultaneously. Partial testing shows that liquidity and profitability have a positive and significant effect on stock returns, but leverage has a negative and significant effect on stock returns. Whereas in the MRA test, it shows that the exchange rate (exchange rate) is not able to moderate liquidity, leverage and profitability on stock returns.